2017
DOI: 10.1126/scisignal.aan0316
|View full text |Cite
|
Sign up to set email alerts
|

Arabidopsis ATXR2 deposits H3K36me3 at the promoters of LBD genes to facilitate cellular dedifferentiation

Abstract: Cellular dedifferentiation, the transition of differentiated somatic cells to pluripotent stem cells, ensures developmental plasticity and contributes to wound healing in plants. Wounding induces cells to form a mass of unorganized pluripotent cells called callus at the wound site. Explanted cells can also form callus tissues in vitro. Reversible cellular differentiation-dedifferentiation processes in higher eukaryotes are controlled mainly by chromatin modifications. We demonstrate that ARABIDOPSIS TRITHORAX-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
63
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 76 publications
(65 citation statements)
references
References 45 publications
1
63
0
Order By: Relevance
“…To generate the mutants, a PCR-based mutagenesis by overlap extension was performed (Lee et al, 2004). The WT and mutated versions of the CDC6 promoter were then cloned into a vector derived from the pCAMBIA1305.1 vector containing the GLUCURONIDASE gene (GUSplus) under the control of a minimal 35S promoter (Lee et al, 2017).…”
Section: Dna Constructs and Plant Transformationmentioning
confidence: 99%
“…To generate the mutants, a PCR-based mutagenesis by overlap extension was performed (Lee et al, 2004). The WT and mutated versions of the CDC6 promoter were then cloned into a vector derived from the pCAMBIA1305.1 vector containing the GLUCURONIDASE gene (GUSplus) under the control of a minimal 35S promoter (Lee et al, 2017).…”
Section: Dna Constructs and Plant Transformationmentioning
confidence: 99%
“…The ARF transcription factors directly bind to the LBD16 and LBD29 promoters and affect LBD expression, consistent with the binding capacity of JMJ30 ( Figure 2c). Moreover, the ARF proteins influence cell fate changes, and accordingly, the arf7-1arf19-2 mutant displays reduction of callus formation (Lee et al, 2017). Therefore, we hypothesized that the ARF transcription factors may recruit JMJ30 and facilitate chromatin modification at associated chromatin regions.…”
Section: Jmj30 Physically Associates With Arf7 and Arf19mentioning
confidence: 99%
“…It has been recently reported that ATXR2 promotes callus formation by stimulating the deposition of H3K36me3 at the LBD16 and LBD29 promoters in developing calli (Lee et al, 2017). Considering that ATXR2 binds the ARF transcription factors and that the JMJ30 and ATXR2 proteins have the same binding capacity to the LBD promoters (Lee et al, 2017), JMJ30 may also work with ATXR2. To test this hypothesis, we examined physical interactions of JMJ30 and ATXR2.…”
Section: Coordinated Actions Of Jmj30 and Atxr2mentioning
confidence: 99%
See 1 more Smart Citation
“…H3K4me3 is typically enriched near the transcription start site and associated with transcriptional initiation, while H3K36me3 is more broadly deposited and associated with transcriptional elongation 38 . Both H3K4me3 and H3K36me3 are linked to various developmental processes and environmental responses 39 and of note, ARABIDOPSIS TRITHORAX-RELATED 2 (ATXR2)mediated H3K36me3 is required for hormone-induced callus formation from Arabidopsis leaf explants 40 . Permissive H3K4me3 and repressive H3K27me3 can co-occur, and this mixed chromatin state is thought to control gene expression during seed development and floral transition 41 .…”
mentioning
confidence: 99%